2021
DOI: 10.3390/nano11092407
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical and Nanotribological Properties of Nanostructured Coatings of Tantalum and Its Compounds on Steel Substrates

Abstract: The present paper addresses the problem of identification of microstructural, nanomechanical, and tribological properties of thin films of tantalum (Ta) and its compounds deposited on stainless steel substrates by direct current magnetron sputtering. The compositions of the obtained nanostructured films were determined by energy dispersive spectroscopy. Surface morphology was investigated using atomic force microscopy (AFM). The coatings were found to be homogeneous and have low roughness values (<10 nm). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…In Figure 1e, the binding energy peaks for metallic Ta and TaN correspond to 22.39 and 23.38 eV, respectively [47]. The positions at 25.18 and 26 eV are attributed to TaON and Ta2O5, respectively [48]. The spectra of N 1s have two peaks located at 401.46 and 397.36 eV.…”
Section: Resultsmentioning
confidence: 96%
“…In Figure 1e, the binding energy peaks for metallic Ta and TaN correspond to 22.39 and 23.38 eV, respectively [47]. The positions at 25.18 and 26 eV are attributed to TaON and Ta2O5, respectively [48]. The spectra of N 1s have two peaks located at 401.46 and 397.36 eV.…”
Section: Resultsmentioning
confidence: 96%
“…The bond energy values confirmed that the Al2O3, coating's chemical composition was close to stoichiometric. In addition, the photoelectron spectra of Ta4f, O1s, N1s of the Ta-based coatings were also registered [4], including the photoelectron lines for Ta (4f7/2) and Ta (4f5/2). Ta +5 signals were recorded at the binding energies of 26.8 eV and 28.7 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, tantalum was also found to be a possible material of choice replacing other extensively used metals for implants in orthopedics. In addition, many studies have shown that tantalum and its compounds demonstrate excellent chemical stability, biocompatibility and antibacterial properties for further use in the medical practice [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of NbN-Ag nanocomposite film are greatly improved via designing the NbN/NbN-Ag multilayer structure. Generally speaking, the wear resistance is strongly dependent upon the film hardness, and the increased hardness could reduce the real contact region with the matched ball [ 3 ], and thus, the hard NbN/NbN-Ag multilayer film exhibited superior wear resistance compared with the soft NbN-Ag nanocomposite film. The predominant wear mechanisms for multilayer film were adhesive wear and oxidation wear, since the Nb, Ag and O elements of film were found on the wear scars of Al 2 O 3 balls (see Figure 10 ), and Nb 2 O 5 as well as AgNbO 3 existed on the wear track of multilayer film.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal nitride films (e.g., TiN, CrN, TiAlN, etc.) fabricated by different physical vapor deposition (PVD) techniques have been widely used for various purposes in the past few decades due to their superior mechanical properties, thermal stability, corrosion resistance and tribological properties [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. However, with the rapid development of modern industry, more and more engineering components are utilized under harsher operating conditions of high speeds and high temperatures [ 8 ]; thus, the traditional nitride films are no longer effective in protecting workpieces due to their poor tribological properties at high-temperature.…”
Section: Introductionmentioning
confidence: 99%